Ginger (Zingiber officinale) as an analgesic and ergogenic aid in sport: a systemic review - Wilson, P. B. (The Journal of Strength and Conditioning Research, 2015)
Ginger is a popular spice used to treat a variety of maladies, including pain. Nonsteroidal anti-inflammatory drugs (NSAIDs) are frequently used by athletes to manage and prevent pain; unfortunately, NSAIDs contribute to substantial adverse effects, including gastrointestinal (GI) dysfunction, exercise-induced bronchoconstriction, hyponatremia, impairment of connective tissue remodeling, endurance competition withdrawal, and cardiovascular disease. Ginger, however, may act as a promoter of GI integrity and as a bronchodilator. Given these potentially positive effects of ginger, a systematic review of randomized trials was performed to assess the evidence for ginger as an analgesic and ergogenic aid for exercise training and sport. Among 7 studies examining ginger as an analgesic, the evidence indicates that roughly 2 g/d of ginger may modestly reduce muscle pain stemming from eccentric resistance exercise and prolonged running, particularly if taken for a minimum of 5 days. Among 9 studies examining ginger as an ergogenic aid, no discernable effects on body composition, metabolic rate, oxygen consumption, isometric force generation, or perceived exertion were observed. Limited data suggest that ginger may accelerate recovery of maximal strength after eccentric resistance exercise and reduce the inflammatory response to cardiorespiratory exercise. Major limitations to the research include the use of untrained individuals, insufficient reporting on adverse events, and no direct comparisons with NSAID ingestion. While ginger taken over 1-2 weeks may reduce pain from eccentric resistance exercise and prolonged running, more research is needed to evaluate its safety and efficacy as an analgesic for a wide range of athletic endeavors.